The Role of Chemokines in Shaping the Balance Between CD4+ T Cell Subsets and Its Therapeutic Implications in Autoimmune and Cancer Diseases - Karin, Nathan; Wildbaum, Gizi (Frontiers in Immunology, 2015)
Chemokines are the key activators of adhesion molecule and also drivers of leukocyte migration to inflammatory sites, and are therefore mostly considered as pro-inflammatory mediators. Many studies, including ours, imply that targeting the function of several key chemokines, but not many others, could effectively suppress inflammatory responses and inflammatory autoimmunity. Along with this a single chemokine named CXCL10 could be used to induce anti tumor immunity, and thereby suppress myeloma. Our working hypothesis is that some chemokines differ from others as aside of being chemo-attractants for leukocytes and effective activators of adhesion receptors that possess additional biological properties making them “driver chemokines”. We came this notion when studying the interlay between CXCR4 and CXCL12 and between CXCR3 and its three ligands: CXCL9, CXCL10 and CXCL11. The current mini-review focuses on these ligands and their biological properties. First we elaborate the role of cytokines in directing the polarization of effector and regulatory T cell subset, and the plasticity of this process. Then we extend this notion to chemokines while focusing on CXCL 12 and the CXCR3 ligands. Finally we elaborate the potential clinical implications of these studies for therapy of autoimmunity, graft versus host disease (GVHD) and cancer.